A strategy to analyze the phenotypic consequences of inhibiting the association of an RNA-binding protein with a specific RNA - Cibois, Marie (Cold Spring Harbor Laboratory Press, 2010)
Targeted inactivations of RNA-binding proteins (RNA-BPs) can lead to huge phenotypical defects. These defects are due to the deregulation of certain mRNAs. However, we generally do not know, among the hundreds of mRNAs that are normally controlled by one RNA-BP, which are responsible for the observed phenotypes. Here, we designed an antisense oligonucleotide (“target protector”) that masks the binding site of the RNA-BP CUG-binding protein 1 (CUGBP1) on the mRNA Suppressor of Hairless [Su(H)] that encodes a key player of Notch signaling. We showed that injecting this oligonucleotide into Xenopus embryos specifically inhibited the binding of CUGBP1 to the mRNA. This caused the derepression of Su(H) mRNA, the overexpression of Su(H) protein, and a phenotypic defect, loss of somitic segmentation, similar to that caused by a knockdown of CUGBP1. To demonstrate a causal relationship between Su(H) derepression and the segmentation defects, a rescue experiment was designed. Embryonic development was restored when the translation of Su(H) mRNA was re-repressed and the level of Su(H) protein was reduced to a normal level. This “target protector and rescue assay” demonstrates that the phenotypic defects associated with CUGBP1 inactivation in Xenopus are essentially due to the deregulation of Su(H) mRNA. Similar approaches may be largely used to uncover the links between the phenotype caused by the inactivation of an RNA-BP and the identity of the RNAs associated with that protein.